Looking at Africa with Lisbon Eyes - The 'wind of change' in the colonial press of Luanda - Rocha, J. M. (Media History, 2021)
Suddenly, in the summer of 1960, the map of Africa gained a new political outline, with the proclamation of nine independences. But the majority of Luanda’s newspapers appeared not to see the ‘wind of change’ blowing through the continent. In its pages, the news of Africa would barely mention more than the crisis in one of its neighbours, the former Belgian Congo. The analysis of the news about the proclamation of independences leads us to formulate the hypothesis that the relative invisibility of the smooth transitions and the major emphasis given to turbulent situations in the continent contributed to value the Portuguese colonial model. Crossing the analysis with research made in archive, this article also contributes to the characterisation of the Angolan daily press on the eve of the Portuguese colonial war.